Novel Bacteriophages Capable of Disrupting Biofilms From Clinical Strains of Aeromonas hydrophila - Kabwe, Mwila; Brown, Teagan; Speirs, Lachlan; Ku, Heng; Leach, Michael; Chan, Hiu Tat; Petrovski, Steve; Lock, Peter; Tucci, Joseph (Frontiers in Microbiology, 2020)
The increase in global warming has favoured growth of a range of opportunistic environmental bacteria and allowed some of these to become more pathogenic to humans. Aeromonas hydrophila is one such organism. Surviving in moist conditions in temperate climates, these bacteria have been associated with a range of diseases in humans, and in systemic infections can cause mortality in up to 46% of cases. Their capacity to form biofilms, carry antibiotic resistance mechanisms, and survive disinfection, has meant that they are not easily treated with traditional methods. Bacteriophage offer a possible alternative approach for controlling their growth. This study is the first to report the isolation and characterisation of bacteriophages lytic against clinical strains of A. hydrophila which carry intrinsic antibiotic resistance genes. Functionally, these novel bacteriophages were shown to be capable of disrupting biofilms caused by clinical isolates of A. hydrophila. The potential exists for these to be tested in clinical and environmental settings.